Answer:
1 7/33
Step-by-step explanation:
6/11 + 2/3 --> We need a common denominator
--> 11 x 3 = 33
33 is our common denominator
6 x 3 = 18
2 x 11 = 22
18/33 + 22/33 = 40/33
Convert to a mixed number
=> 1 7/33
Thus, we have our answer.
Answer:
B
Step-by-step explanation:
Answer:
<h2>1.04</h2>
Step-by-step explanation:
<h2>Hope this helps. Mark as brainlest plz!</h2>
Use substitution.
y = 2 - x and y = 4x + 7 can become
2 - x = 4x + 7
Now solve for x
-5 = 5x
-1 = x
Now plug -1 for x in either equation.
y = 2 - x -> y = 2 - (-1) -> y = 3
y = 4x + 7 -> y = 4*-1 + 7 -> y = -4 + 7 -> y = 3
So C) is the correct answer.